Laminar Pattern of Projections Indicates the Hierarchical Organization of the Anterior Cingulate-Temporal Lobe Emotion System - Sakata, Honami; Kim, Yuri; Nejime, Masafumi; Konoike, Naho; Miyachi, Shigehiro; Nakamura, Katsuki (Frontiers in Neuroanatomy, 2019)
The anterior cingulate cortex (ACC), surrounding the genu of the corpus callosum, plays important roles in emotional processing and is functionally divided into the dorsal, perigenual, and subgenual subregions (dACC, pgACC, and sgACC, respectively). Previous studies have suggested that the pgACC and sgACC are involved in mood disorders in different manners. Anatomically, the ACC has rich connections with other emotion-related areas including the amygdala and the medial temporal and temporal pole (TP) areas. To understand the neuroanatomical basis of the functional differences between the ACC subregions, we injected neuronal tracers into the pgACC, sgACC, and dACC and compared the afferent connections. Previously, we analyzed the afferent projections from the amygdala, and found a distinct pattern for the sgACC. In the present study, the patterns of the afferent projections were analyzed in the temporal pole and medial temporal areas. After injections in the sgACC, many labeled neurons were found in the TP and the subiculum of the hippocampal formation. In the TP, a majority of the labeled cell bodies was found in the superficial layers (“feedforward” type projections). The pgACC received afferent projections from the TP, the entorhinal cortex, and the parahippocampal cortex, but not from the hippocampus. In each area, the labeled cells were mainly found in the deep layers (“feedback” type projection). The pattern for the dACC was similar to that for the pgACC. Within the ACC, the projections from the sgACC to the pgACC originated predominantly in the deep layers (“feedback” type projection). These data suggest that the sgACC ranks higher than the pgACC in the hierarchy of the emotional system.